Implementation of the Mayor's Policy on the Regulation of Street Vendors Along Mardika Market Street - Kisman Ady; Moh. Daud Marasabessy; Ruslan Rumbati (Univiversitas Dr. Djar Wattiheluw, 2024)
Frequent traffic congestion at Mardika Market in Ambon City is primarily caused by the disorganized activities of street vendors (PKL), which has become a significant concern for the government. This study aims to evaluate the policy implementation process for controlling street vendors by the Ambon City Civil Service Police Unit, focusing on four key indicators: communication, resources, implementers' attitudes, and bureaucratic structure. Using a descriptive approach, data were collected through interviews and observations. The findings indicate that while the policy has been implemented in terms of communication efforts with vendors, available resources—such as personnel—remain insufficient, although other resources are adequate. The attitudes of implementers were largely supportive, with 97% in favor and 3% not supportive. The bureaucratic structure, governed by Standard Operating Procedures (SOPs), has been less effective due to conflicts over the timing of enforcement. As a result, the implementation has not been fully effective, as traffic jams persist due to vendors occupying the streets.